2013
DOI: 10.3109/09273948.2013.840385
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Presentation of Posterior Scleritis: A Report of 31 Cases

Abstract: Posterior scleritis must be considered in patients with decrease of vision, mild to severe pain, optic disc edema, and/or posterior uveitis. Moderate to severe pain may be associated with poorer visual outcome.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
36
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(37 citation statements)
references
References 12 publications
1
36
0
Order By: Relevance
“…The current study showed female preponderance which was in accordance with the other case series on posterior scleritis. [ 5 6 7 8 ] Compared to other subtypes of scleritis, the posterior scleritis usually occurs in patients with relatively younger age. [ 3 9 ] The mean age of our patients in this study (41.2 years) was comparable to similar studies on posterior scleritis[ 7 ] and was in accordance with finding of the study by Lavric et al .,[ 5 ] where a relatively younger age of involvement in posterior scleritis was reported in Indian patients when compared with patients from the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…The current study showed female preponderance which was in accordance with the other case series on posterior scleritis. [ 5 6 7 8 ] Compared to other subtypes of scleritis, the posterior scleritis usually occurs in patients with relatively younger age. [ 3 9 ] The mean age of our patients in this study (41.2 years) was comparable to similar studies on posterior scleritis[ 7 ] and was in accordance with finding of the study by Lavric et al .,[ 5 ] where a relatively younger age of involvement in posterior scleritis was reported in Indian patients when compared with patients from the United Kingdom.…”
Section: Discussionmentioning
confidence: 99%
“…Posterior scleritis may cause serous retinal detachments, optic disc edema, and chorioretinal granulomas. 46,99 …”
Section: Posterior Scleritismentioning
confidence: 98%
“…Four to ten percent of scleritis is infectious in origin, 46,92,133 with recent surgery and trauma as the most common cause. 27,55,59, 148 Post-surgical and post-traumatic causes of scleritis are generally bacterial in nature, upwards of 45% of all cases.…”
Section: Infectious Scleritismentioning
confidence: 99%
See 1 more Smart Citation
“…The first presentations, including loss of vision accompanied by pain in the eye, suggested in fact ON [8] or posterior scleritis (PS) [9].…”
Section: Discussionmentioning
confidence: 99%